{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

2009a_x1a_sols - E ÜaÑ Ó ÐÙ Ø iÓÒ × F Ó ÖÑA C a...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: E ÜaÑ Ó ÐÙ Ø iÓÒ × F Ó ÖÑA C a- 2 b = < 2 , 3 >- < 2 ,- 4 > = < , 7 > E a i×Ó ÖØhÓgÓÒa ÐØÓ b Ñ eaÒ a · b = 0 ×Ó ( s )(- 1) + 2 t = 0 Ó Ö s = 2 t E h eeÕÙa Ø iÓÒÓ fØh e ÐiÒ e i×g iÚ eÒbÝ r ( t ) = r + t v , Û h eÖe r = < 1 ,- 1 > aÒd v = <- 2 , 3 > ×Ó Øh eeÕÙa Ø iÓÒ i× r ( t ) = < 1 ,- 1 > + t <- 2 , 3 > Ó Ö r ( t ) = < 1- 2 t,- 1 + 3 t > 4 C ÓÒdaÔa Öa ÐÐe ÐÙÒ iØÚ eØÓ ÖÑ Ù ÐØ iÔ ÐÝ Øh eg iÚ eÒÚ eØÓ ÖbÝ Øh eÖe iÔ ÖÓa ÐÓ fiØ×Ñ agÒ iØÙd e h eÖe×Ù ÐØ i× 1 radicalbig 2 2 + (- 1) 2 (2 i- j ) = 1 √ 5 (2 i- j ) 5 D h eC a ÖØe× iaÒeÕÙa Ø iÓÒ i×ba ×edÓÒ Øh e id eÒ Ø iØÝ cos 2 t + sin 2 t = 1 iÒe cos t = 2 x aÒd sin t = y Øh e id eÒ Ø iØÝb eÓÑ e× (2 x ) 2 + y 2 = 1 Ó Ö 4 x 2 + y 2 = 1 6 D F aØÓ ÖaÒdaÒe Ð: lim x → 3 ( x- 2)( x- 3) ( x + 3)( x- 3) = lim x → 3 x- 2 x + 3 = 1 6 7 A F aØÓ ÖÓÙ ØØh edÓÑ iÒa Ø iÒg ØeÖÑ ×ieh igh e×ØÔÓÛ eÖ×Ó...
View Full Document

{[ snackBarMessage ]}